The psycho-pedagogical approach to brain damage acquired in childhood - Rizky Pratama, Ahmad; Rahmawati, Siti; Fajar Hidayat, Muhammad; Binti Ahmad, Nur Aisyah; Hafiz Ismail, Muhammad; Martínez Gómez, Laura; Morales Fernández, Javier (International Journal of Neurology, 2024)
Introduction: This study addressed acquired brain injury (ABI) in childhood as an increasingly relevant issue in the fields of health and education, due to its significant impact on children’s cognitive, emotional, and behavioral development. It was considered that, as it occurs in a developing brain, ABI generates complex consequences that directly affect learning processes and the acquisition of Basic Learning Devices (BLDs), which justified its analysis from a psychopedagogical perspective. Development: The research analyzed the concept of ABI and its main etiologies in the child population, such as traumatic brain injury, stroke, anoxia, brain tumors, epilepsy, and central nervous system infections. The associated physical, cognitive, emotional, and behavioral sequelae were described, highlighting alterations in attention, memory, executive functions, and language. Likewise, learning was examined as a complex process, influenced by neurophysiological, subjective, and contextual factors, and DBA—motivation, attention, sensory perception, memory, and habituation—were explored in depth as indispensable conditions for learning to occur. Within this framework, the role of psychopedagogy and psychopedagogical interventions within interdisciplinary and transdisciplinary approaches was analyzed. Conclusions: It was concluded that childhood ACD significantly affected children’s learning processes and overall development, requiring specific, comprehensive, and sustained psychopedagogical interventions aimed at enhancing preserved abilities, promoting educational inclusion, and supporting families and educational institutions.